Польское прочтение русской мысли в п осткоммунистический период (эскиз) - de Lazari, Andrzej (Przegląd Rusycystyczny, 2020)
The article shows some major bibliographical items discussing the condition of Polish research on Russian thought after 1989. It also describes that research paying special attention to the world view of Polish researchers